Effect of source and drain asymmetry on hot carrier degradation in vertical nanowire MOSFETs. Issue 9 (August 2015) - Lee, Jae Hoon; Han, Jin-Woo; Yu, Chong Gun; Park, Jong Tae
Abstract: Effects of source and drain (S/D) asymmetry on hot carrier degradation in vertical nanowire MOSFETs have been investigated with different nanowire radiuses. The S/D asymmetry causes different degree of hot carrier degradations between forward and reverse stresses. The actual stress voltage applied to the channel as a result of parasitic resistance and gate to junction overlap length is attributed to the cause of the asymmetric degradation. The narrower nanowire also suffers from worse hot carrier effects due to current crowding and geometric effects. Highlights: Investigation of the effects of source and drain asymmetry on HC degradation in vertical nanowire MOSFETs Increased HC degradation in reverse mode is due to actual stress voltage applied to the channel and a conical shape of pillar. Increased HC degradation with decreasing nanowire radius may be attributed to the current crowding and geometric effects.